Shakan pitfall traps: hunting techniques in the Zulu Kingdom - Hall, M. (Southern African Humanities, 2021)
The results of excavations of pitfall traps are described. These were located in the Umfolozi Game Reserve, Zululand, and had been used by the Zulu King, Shaka, in the early nineteenth century. By integrating these archaeological data with ethnographic evidence and oral histories it is possible to learn something of hunting techniques in the later Iron Age. To cite this article: Hall, M. 1977. Shakan pitfall traps: hunting techniques in the Zulu Kingdom. Annals of the Natal Museum 23 (1): 1-12.